Monophyly of four sections of genus Dendrobium (orchidaceae): evidence from nuclear ribosomal DNA intrenal transcribed spacer (ITS) sequences - Moudi, Maryam; Go, Rusea (Ebioscholar, 2015)
Evolutionary relationship among four sections of the genus Dendrobium (Aporum, Crumenata, Strongyle and Bolbidium) were inferred from nucleotide sequence variation in nuclear ribosomal DNA of Peninsular Malaysia species. The Internal transcribed spacer (ITS) of nuclear ribosomal DNA from representative of 29 species of genus Dendrobium and two species of genus Bulbophyllum as out group were analyzed by polymerase chain reaction amplification and DNA sequencing. Data analyses have been carried out using Maximum Parsimony (MP) as a character based method by different software (PAUP*4. 0 B 10 and Mega 5). Parsimony analyses of sequences resulted in a well-resolved phylogeny. The data suggested that Internal Transcribed Spacer (ITS) is a reliable marker for the phylogenetic study of Dendrobium compared to previous studies using chloroplast DNA with low resolution level among sections. The results demonstrated that the four sections formed a monophyletic group and that it is best to recognise only one section instead of four. Based on ICBN rules, the name Aporum has a priority to be used for this new classification.